2013
DOI: 10.1016/j.jbi.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Classifying temporal relations in clinical data: A hybrid, knowledge-rich approach

Abstract: We address the TLINK track of the 2012 i2b2 challenge on temporal relations. Unlike other approaches to this task, we (1) employ sophisticated linguistic knowledge derived from semantic and discourse relations, rather than focus on morpho-syntactic knowledge; and (2) leverage a novel combination of rule-based and learning-based approaches, rather than rely solely on one or the other. Experiments show that our knowledge-rich, hybrid approach yields an F-score of 69.3, which is the best result reported to date o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…27 33 41 Other third party temporal expression taggers, SUTIME 42 and GUTIME, 30 were utilized by others. 38 Despite some success in utilizing existing systems, most teams developed their own frequency detection and normalization components.…”
Section: Event/timex3 Trackmentioning
confidence: 99%
“…27 33 41 Other third party temporal expression taggers, SUTIME 42 and GUTIME, 30 were utilized by others. 38 Despite some success in utilizing existing systems, most teams developed their own frequency detection and normalization components.…”
Section: Event/timex3 Trackmentioning
confidence: 99%
“…The study demonstrated that adding syntactic features results in a considerable improvement over the state-of-the-art methods of temporal relations classification. D’Souza et al [107] classified TLINKs using PropBank-style predicate-argument relations, and discourse relations. TLINK represents the temporal relation that holds between events, times or between an event and a time with different subsets of values (simultaneous, before, after, etc.)…”
Section: Extraction Of Temporal Informationmentioning
confidence: 99%
“…The 2012 Informatics for Integrating Biology and the Bedside (i2b2) challenge [121] marked a shift in the wide community in the sense that it refocused the research initiative towards temporal relation extraction from newswire data to data from the clinical domain [107]. Twenty teams representing 23 organizations and nine countries have participated in the medication challenge.…”
Section: Extraction Of Temporal Informationmentioning
confidence: 99%
“…Most state-of-the-art systems presented for the 2012 i2b2 clinical NLP challenge used machine learning-based methods to extract relationships between events and DCT [23, 24]. For example, the best system proposed by Tang et al adopted SVMs [23].…”
Section: Related Workmentioning
confidence: 99%